About some options of the probability theory of description of motion of space vehicle - Ракишев, Ж; Аппазова, Ш; Бейсембаева, Б (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
While controlling a spacecraft (controlling the motion of the center of mass), the problem of correcting its orbit arises. Options of define the spacecraft motion, which depend on its own speed and on the Earth’s gravitational forces effect radius, are considered. In this paper we propose an approach that can significantly improve the reliability of the trajectory calculation, thereby reducing thereby reducing the probability of non-anticipated emergencies during their operation.